Numerical analysis in Ar-H2 coupled-coil inductively coupled thermal plasma with Si feedstock for stable operation - Yulianta Siregar; Yasunori Tanaka (Institute of Advanced Engineering and Science, 2023)
In nanopowder synthesis, the starting powder to be evaporated is infused in a plasma torch through the upper coil and the lower coil in the coupled model of inductively coupled thermal plasma (coupled-coil inductively coupled thermal plasma (ICTP)). Mixing these evaporated materials to form the coupled ICTP significantly influences the thermodynamic and transport properties. It is essential to understand these complex interactions between coupled ICTP and feedstock evaporation. This research investigated the thermal interactions between silicon raw material powder (Si) with ICTP in coupled 99%Ar/1%H2 through the numerical model developed for the synthesis of Si nanopowder. The feed rate of the Si raw material was set at 0.05, 0.1, and 0.5 g/min. This implies that the increased Si feed is too heavy to vaporize all the injected feed.